Harnessing "Lost Rainfall" for Crop Production - Jenkins, William J. (Indian Forester, 1944)
By contour bunding and scientific dry farming methods, the Government of Bombay is launching a great campaign to fight recurring famines over large tracts of the "dry" areas of the province. Every effort is being "'made to utilize the "lost rainfall" for profitable crop production and also to check the severe annual loss of fertile surface soil. In the accompanying article, the author tells us how all this is being done.